Composite Corundum Ceramics with Reinforcing Carbon Nanotubes Modified with Eutectic Additives - Antonov Dmitriy (EDP Sciences, 2021)
The characteristics of composite materials of Al2O3 system - carbon nanotubes - eutectic additives are investigated. The influence of the reinforcing component content, as well as the mode of high-temperature heat treatment in vacuum on the strength properties of the material are considered. Samples with a mass content of carbon tubes of 0.4% were obtained. These samples had the following characteristics: an average tensile strength at three-point bending of 380 MPa, an open porosity of 0.9%, an average density of 3.71 g/cm3.